(La1‐xMx)2(Nb0.45Yb0.55)2O7‐δ (M=Ca, Sr, Ba) Ionic Conductors Promoted by Foreign/Domestic Dual Acceptor‐Doping Strategies. Issue 24 (11th November 2022) - Zhang, Xiaorong; Jiang, Lulu; Guo, Shihang; Han, Donglin
Abstract: In this work, a class of ionic conductor (La1‐ x M x )2 (Nb0.45 Yb0.55 )2 O7‐ δ (M=Ca, Sr, and Ba) with a cubic pyrochlore structure was reported. Two strategies were adopted to increase the concentration of oxygen vacancies favoring the hydration reaction to introduce protons. One was increasing the cation ratio between Yb and Nb over unity, the other was doping divalent alkaline earth elements to replace trivalent La. Proton conduction was evidenced by confirming the proton incorporation and H/D isotope effect in electrical conductivity. Doping Ca, Sr, and Ba further promoted the proton conduction. The results of crystal structure refinement indicated that the extrinsically introduced oxygen vacancies by the two strategies were accommodated in the tetrahedra (48  f ) containing two La and two Yb/Nb cations, while the tetrahedra containing four La cations (8 a ) were fully occupied by oxide ions. A discussion was thereby performed, leading to the suggestion that not all the tetrahedra in the cubic pyrochlore structure of (La1‐ x M x )2 (Nb0.45 Yb0.55 )2 O7‐ δ helped in incorporating and conducting protons, and only the oxygen vacancies surrounded by four Y cations (48  f site) or two La and two Y cations (8 b site) were hydratable. It is thereby suggested that to enhance the proton conduction in pyrochlore oxides, an effective strategy might be tuning the ability of hydration or protonation of the tetrahedra to increase the proton concentration and expand the route for proton conduction. Abstract : Proton conduction : A new ionic conductor of (La1‐ x M x )2 (Nb0.45 Yb0.55 )2 O7‐ δ (M=Ca, Sr, Ba) with a cubic pyrochlores crystal structure is reported. In this material, only the tetrahedra containing four Y cations or two La and two Y cations are suggested to contribute to the hydration reaction, which promotes the proton conduction.